2008
DOI: 10.1159/000151572
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Microvessel Density and the Expression of Lymphangiogenic Factors in Oral Squamous Cell Carcinoma

Abstract: Objective: In this study, the expression of several lymphangiogenic growth factors was investigated to determine the mechanism underlying lymphangiogenesis in oral squamous cell carcinoma (OSCCa). Materials and Methods: An immunohistochemical study was performed to determine the lymphatic microvessel density (LMVD) and the expression of vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), basic fibroblast growth factor (bFGF), insulin-like growth factors (IGF-I/II), and hepatocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…in 2003,[16] Zheng-Jun et al . in 2007,[17] Ali in 2008[18] who concluded that VEGF expression in OSCC triggers lymphatic angiogenesis, which may result in higher risk for lymph node metastasis. The angiogenic effects of VEGF may also favor the onset of late lymphatic and hematogenous metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…in 2003,[16] Zheng-Jun et al . in 2007,[17] Ali in 2008[18] who concluded that VEGF expression in OSCC triggers lymphatic angiogenesis, which may result in higher risk for lymph node metastasis. The angiogenic effects of VEGF may also favor the onset of late lymphatic and hematogenous metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor model overexpression of HGF was found to induce lymphatic vessel growth in the peritumoral region [14] and in human oral SCC a significant correlation was detected between LVD and HGF expression [31]. In contrast, in high grade salivary carcinomas absence of correlation between HGF expression in tumor cells and regional lymph node and distant metastasis has been reported [32].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between LMVD and poor prognosis of tumor patients has been identified in breast cancer, prostate adenocarcinoma, colon cancer, melanoma, NSCLC and oral squamous cell carcinoma (20)(21)(22)(23)(24). However, the correlation between LMVD status (intratumoral or peritumoral) and tumor prognosis has not yet been fully clarified.…”
Section: Discussionmentioning
confidence: 99%